Adaptation to Visuomotor Rotations Remaps Movement Vectors, Not Final Positions - Wang, Jinsung (J Neurosci, 2005)
When exposed to novel visuomotor rotations, subjects readily adapt reaching movements, such that the virtual display of the hand is brought to the target. Whereas this clearly reflects remapping of the relationship between hand movements and the visual display, the nature of this remapping is not well understood. We now examine whether such adaptation results in remapping of the position of the visually displayed target and the final limb position or between the target vector and the movement vector. The latter is defined relative to a starting position, whereas the former should be independent of the starting position. Subjects first adapted to a 30° rotation during reaching movements made from a single starting location to four different target locations. After adaptation, generalization trials were introduced, during which reaching movements were made under the same visual rotation condition but started from one of two locations outside the practiced workspace. These trials were directed to either the previously practiced targets or new targets that reflected the direction and distance of the practiced trials. Generalization was greatest for movements made in similar directions, regardless of changes in spatial location. Most significantly, when reaching to the previously adapted targets, subjects did not reach to the previously learned limb positions but rather to positions that reflected a near 30° rotation of the new target vector. These results indicate that learned visuomotor rotations remap the representations of movement vectors and not final positions of the limb in the workspace.